The Emergence of Fusarium oxysporum f. sp. apii Race 4 and Fusarium oxysporum f. sp. coriandrii Highlights Major Obstacles Facing Agricultural Production in Coastal California in a Warming Climate: A Case Study - Epstein, Lynn; Kaur, Sukhwinder; Henry, Peter M. (Frontiers in Plant Science, 2022)
Currently, Fusarium oxysporum f. sp. apii (Foa) race 4 in celery and F. oxysporum f. sp, coriandrii (Foci) in coriander have the characteristics of emerging infectious plant diseases in coastal, southern California: the pathogens are spreading, yield losses can be severe, and there are currently no economical solutions for their control. Celery, and possibly coriander, production in these regions are likely to have more severe disease from projected warmer conditions in the historically cool, coastal regions. Experimental evidence shows that Foa race 4 causes much higher disease severity when temperatures exceed 21°C. A phylogenomic analysis indicated that Foa race 4, an older, less virulent and uncommon Foa race 3, and two Foci are closely related in their conserved genomes. These closely related genotypes are somatically compatible. Foa race 4 can also cause disease in coriander and the two organisms readily form “hetero” conidial anastomosis tubes (CAT), further increasing the likelihood of parasexual recombination and the generation of novel pathotypes. A horizontal chromosome transfer event likely accounts for the difference in host range between Foci versus Foa races 4 and 3, because they differ primarily in one or two accessory chromosomes. How Foa race 4 evolved its hyper-virulence is unknown. Although the accessory chromosomes of Foa races 3 and 4 are highly similar, there is no evidence that Foa race 4 evolved directly from race 3, and races 3 and 4 probably only have a common ancestor. Foa race 2, which is in a different clade within the Fusarium oxysporum species complex (FOSC) than the other Foa, did not contribute to the evolution of race 4, and does not form CATs with Foa race 4; consequently, while inter-isolate CAT formation is genetically less restrictive than somatic compatibility, it might be more restricted between FOSC clades than currently known. Other relatively new F. oxysporum in coastal California include F. oxysporum f. sp. fragariae on strawberry (Fof). Curiously, Fof “yellows-fragariae” isolates also have similar core genomes to Foa races 4 and 3 and Foci, perhaps suggesting that there may be core genome factors in this lineage that favor establishment in these soils.